Hubungan Penggunaan KB Suntik DMPA Terhadap Indeks Massa Tubuh (IMT) - Widya Kusumawati; Lely Khulafa’ur Rosidah (Poltekkes Kemenkes Denpasar, 2021)
More than six million women worldwide use the injectable hormonal contraceptive method (Fraser, 2011). The DMPA hormone which contains progesterone can affect the fat layer and appetite which will affect weight gain which has an impact on body mass index (Helti Lestari S., 2019). The purpose of this study was to determine the relationship between the use of DMPA injections on BMI. This research method is analytic with cross sectional approach. It was conducted in Ngampel sub-district, Mojoroto sub-district, Kediri city in June – July 2019. The study population was all women of EFA, with purposive sampling technique, a total of 30 respondents were obtained. The variable of this study was the use of DMPA injectable contraception and the dependent variable was BMI. The research instrument used a questionnaire, and the type of data taken was quantitative data. Data analysis using Chi Square with a significance level = 0.05. The results showed that from 30 respondents 19 respondents (63.33%) used non-hormonal family planning 7 (23.33%) with normal BMI and 12 (40%) BMI Obesity, while DMPA injection family planning acceptors 2 (6.66%) BMI Normal, 11 (30%) BMI Obese. Based on the analysis, the value of 2 count = 1.14 2 tables = 3.84, which means that there is no relationship between the use of DMPA injecting family planning and BMI. Although the use of DMPA injectable contraception is not related to BMI, the body should be given rest time using non-hormonal family planning (MKJP: IUD and Tubectomy / Vasectomy).